Changes of occupational class differences in physical functioning: a panel study among employees (2000–2007). Issue 3 (5th October 2010) - Pietiläinen, Olli; Laaksonen, Mikko; Pitkäniemi, Janne; Rahkonen, Ossi; Lahelma, Eero
Abstract : Background: Panel studies on changes of occupational class differences in health have given varying results. The aim of this study was to examine changes of occupational class differences in physical functioning and the factors that explain these changes. Methods: A cohort of middle-aged employees of the City of Helsinki was followed up for an average of 6 years in two surveys from 2000–2002 and 2007. Hierarchical linear random effects models were fitted to analyse the changes of occupational class differences in SF-36 physical functioning, as well as the contribution of physical and psychosocial working conditions, material conditions, health behaviours and employment status to these changes. Results: Lower occupational classes had worse physical functioning at baseline: among women, the SF-36 scores ranged from 50.5 in the highest class to 47.1 in the lowest one, and among men from 52.2 to 48.9, with higher scores indicating better health. Occupational class differences widened during the follow-up due to stronger decline of physical functioning in the lower occupational classes than in the higher occupational classes. The largest difference in the decline of functioning between classes was 1.2 scores among women and 1.5 scores among men. Among women the widening of the class differences could be explained partly by health behaviours and employment status and among men by material conditions. Conclusion: Occupational class differences in physical functioning widened due to a faster decline of physical functioning in the lower occupational classes. Health behaviours, employment status and material conditions explained the widening class differences in physical functioning.